The Effectiveness of AI-Assisted Reading Tools on EFL Students’ Reading Comprehension and Engagement - Nasmah Riyani riyan (Universitas Islam Negeri Palopo, 2025)
This study investigates the effectiveness of a ChatGPT-based Reading Assistant in enhancing EFL students’ reading comprehension and learning engagement. Employing a quasi-experimental design, the study involved two groups of third-semester undergraduate students during the 2024/2025 academic year. Over a six-week instructional period, the experimental group received reading instruction supported by the ChatGPT Reading Assistant, while the control group followed conventional reading practices. Data were collected using a standardized reading comprehension test and an engagement questionnaire. An independent samples t-test revealed no statistically significant difference between the groups’ pretest scores (p > .05), indicating comparable initial proficiency. Post-intervention analysis showed that the experimental group outperformed the control group in reading comprehension, with a statistically significant difference (p < .05). Engagement levels were also significantly higher in the experimental group compared to the control group (p < .05). These findings suggest that AI-assisted reading tools can effectively support EFL reading instruction by improving comprehension outcomes and fostering greater student engagement. Further research is recommended to investigate long-term instructional impacts and to explore learners’ qualitative experiences with AI-supported reading activities.